Proceedings of the 20th ACM Conference on Hypertext and Hypermedia 2009
DOI: 10.1145/1557914.1557948
|View full text |Cite
|
Sign up to set email alerts
|

Games with a purpose for social networking platforms

Abstract: The online games market has matured in recent years. It is now a multi-billion dollar business with hundreds of millions players worldwide. At the same time, social networking platforms have witnessed unprecedented growth rates and increasingly offer developer interfaces to leverage and extend their built-in core functionality. Benefiting from these trends, games with a purpose are a proven way of leveraging the wisdom of the crowds to address tasks that are trivial for humans but still not solvable by compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 7 publications
0
39
0
Order By: Relevance
“…Through their social game Magpies, also on Facebook, Kirman et al [17] found that the additional sociocontextual data such as social network analysis (SNA) information can increase the frequency of social activity between players engaged in the game but does little to increase the growth of the player-base. Similar to this paper, Rafelsberger and Scharl [18] propose an application framework to develop interactive games with a purpose on top of social networking platforms, leveraging the wisdom of the crowd by engaging users in online games to complete tasks that are trivial for humans but difficult for computers. In this paper, we leverage the social aspects of OSNs both to recruit human trainers and to improve the performance of the agents they train.…”
Section: B Social Networkmentioning
confidence: 99%
“…Through their social game Magpies, also on Facebook, Kirman et al [17] found that the additional sociocontextual data such as social network analysis (SNA) information can increase the frequency of social activity between players engaged in the game but does little to increase the growth of the player-base. Similar to this paper, Rafelsberger and Scharl [18] propose an application framework to develop interactive games with a purpose on top of social networking platforms, leveraging the wisdom of the crowd by engaging users in online games to complete tasks that are trivial for humans but difficult for computers. In this paper, we leverage the social aspects of OSNs both to recruit human trainers and to improve the performance of the agents they train.…”
Section: B Social Networkmentioning
confidence: 99%
“…Human language technology games integrated into social networking sites such as Sentiment Quiz [63] on Facebook show that social interaction within a game environment does motivate players to participate. The Sentiment Quiz asks players to select a level of sentiment (on a 5 point scale) associated with a word taken from a corpus of documents regarding the 2008 US Presidential election.…”
Section: Sentiment Analysismentioning
confidence: 99%
“…We will extend our game portfolio with new Facebook-based games similar to the already successfully deployed Sentiment Quiz (Rafelsberger and Scharl, 2009). The Sentiment Quiz addressed major challenges of GWAPs such as how to attract and retain players, how to ensure the generation of high quality data, and how to effectively aggregate results.…”
Section: Low-overhead Forms Of User Feedbackmentioning
confidence: 99%